2015
DOI: 10.1089/gtmb.2014.0292
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA Methylation in Plasma for Monitoring Hepatocarcinogenesis

Abstract: These results suggested that the methylation of tumor suppressor genes may participate in the development and progression of HCC. Additionally, it may be useful to combine the plasma DNA methylation status of a panel of gene markers and the serum AFP for HCC screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 39 publications
(46 reference statements)
2
23
0
3
Order By: Relevance
“…This finding is consistent with Araújo and Gioia et al [25,26] who reported an increase in RASSF1A PM with progression from regenerative conditions (e.g. cirrhosis) to hepatocellular nodules and HCC, as well as with Huang et al [15] and Chan et al [27] who reported RASSF1A methylation in the blood and tissues of HCC patients. Our results also showed an increasing frequency of p16 PM from NHT to HCC which is in agreement with the earlier studies [28,29].…”
Section: Normal Liver N = 13 (%) Chronic Hepatitis (Ch)supporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with Araújo and Gioia et al [25,26] who reported an increase in RASSF1A PM with progression from regenerative conditions (e.g. cirrhosis) to hepatocellular nodules and HCC, as well as with Huang et al [15] and Chan et al [27] who reported RASSF1A methylation in the blood and tissues of HCC patients. Our results also showed an increasing frequency of p16 PM from NHT to HCC which is in agreement with the earlier studies [28,29].…”
Section: Normal Liver N = 13 (%) Chronic Hepatitis (Ch)supporting
confidence: 91%
“…The positive predictive value (PPV) was higher than the negative predictive value (NPV) for APC, FHIT, p16, and E-cadherin whereas, the negative predictive value was higher for p15 ( Table 1). Therefore, a previous study by Huang et al, [15] concluded that it may be useful to combine the plasma DNA methylation status of ELF, RASSF1A, p16, and GSTP1 with serum AFP for HCC screening and several studies had confirmed these data [16,17]. However controversial results were reported by Chang et al [18] who found no agreement between plasma and tissue DNA samples.…”
Section: Concordance Between Tissue and Plasma Dna Methylation In Hccmentioning
confidence: 99%
“…Анализ уровня метилирования сайтов в промоторах генов CDKN2A и CDKN2В в комбинации с другими биомаркерами метилирования в ц-ДНК из плазмы или сыворотки крови пациентов с ГК характеризуется высокими (84,0-93,6 %) показателями чувствительности для диагностики ГК [55,56]. Гиперметилирование сайтов в промоторе гена CDKN2A в ц-ДНК также рассматривается в качестве потенциального диагностического биомаркера, показатели чувствительности и специфичности которого составляют 47,8-73,0 и 82,6-87,2 % соответственно [54,57,58].…”
Section: обзорные статьиunclassified
“…В то же время для пациентов с HBV-ассоциированными ГК индивидуальная диагностическая значимость метилирования сайта в промоторе GSTP1 невысока [34]. Этот биомаркер может быть использован для диагностики ГК в составе мультигенных панелей: по данным W. Huang и соавт., такая мультигенная панель отличается более высоким показателем чувствительности (93,6 %) по сравнению с АФП (48,4 %) [56].…”
Section: обзорные статьиunclassified
“…Numerous studies have confirmed that using DNA methylation changes as biomarkers for carcinoma is useful for early detection of cancer, including HCC [11]. For example, aberrant methylation of serum ELF, RASSF1A, GSTP1, APC, SFRP1, LINE-1, GRA has been shown to be useful as biomarkers for assessing the risk of HCC [12][13][14][15][16]. Abnormal hypermethylation of a CpG island in different stages of tumorigenesis is a dysfunction of tumor suppressor genes (TSGs) [17][18][19].…”
mentioning
confidence: 97%